Tutela, stile, autografia. Ontologia dei beni culturali e architettura - Davide Grasso (Rivista di Estetica, 2012)
Institutions are committed to a constant work aimed at classifying cultural heritages, in order to preserve selected objects from decay or disappearing. In this domain of policy, a significant role is played by architecture and by the preservation of the architectural heritage of cities. How is it possible, however, to determine the value in the field of architectural heritages? What are the criteria for evaluation and the degree of objectivity these classifications are based upon? Is architectural worth immanent to objects or does it reside outside them? These are fundamental questions for the science of preservation and the legislation on cultural heritages. By closely examining a controversial case occurred in the European Union, e.g. England, the paper tackles analytically some of these issues, and it exploits also concepts borrowed from social ontology and ontology of art.